Mutual Trade and Cross-Border Economic Interaction of Ukraine and Slovak Republic - Lačný, Martin (Journal of Economic Development, Environment and People, 2017)
The Slovak-Ukrainian border, as well as mutual economic interaction has been changing in the course of the following periods: a) 1993-2004: the bilateral intergovernmental regime of the border; b) 2004-2016: the community regime of the border between the EU and Ukraine, and c) the new border regime after the signing and subsequent implementation of the Association Agreement between the EU and Ukraine, including the Deep and Comprehensive Free Trade Area Agreement (DCFTA) as well as an agreement on visa-free regime between the EU and Ukraine. Within the outlined context the paper seeks to explore the history and dynamics of Slovak-Ukrainian mutual economic interaction, as well as the recent conditions in the CBC area, understanding of which may contribute to building capacities of CBC actors to make best use of opportunities brought by AA/DCFTA and thus consequently to boost economic development of the Slovak-Ukrainian borderland regions.